The Role Of Production Process And Product Quality On Business Success: A Case Study On The Lamongan Planting Micro Business - Dikki Permana Saputra; Muhammad Daffa Egy; Mashudi (Managing: Jurnal Bisnis dan Manajemen, 2026)
This study aims to analyze the influence of production processes and product quality on the success of the Penyetan Lamongan culinary MSME. Based on data collected through interviews and direct observation, the findings indicate that production efficiency and consistent product quality in terms of hygiene, taste, and presentation significantly contribute to customer satisfaction and business competitiveness. The implementation of simple yet consistent strategies in managing production and quality has proven effective in supporting the sustainability of this small-scale culinary enterprise.